554 Biopsar study: ultrasound-guided preoperative biopsy to assess histology of sarcoma-suspicious uterine tumors. a new study protocol. (4th December 2020) - Petousis, Stamatios; Croce, Sabrina; Kind, Michel; Lalet, Caroline; Babin, Guillame; Margioula-Siarkou, Chrysoula; Querleu, Dennis; Floquet, Anne; Pulido, Marina; Guyon, Frederic
Abstract : Topic: Trials in progress abstract Introduction/Backgroun: The preoperative differential diagnosis between a uterine fibroma and a sarcoma is a challenge. Available diagnostic tools are rather inconclusive to distinguish between two pathologies. However, potential accurate diagnostic methods would be of great clinical impact in order to optimize surgical treatment. Methodology: A prospective multi-center interventional study will be performed. Ten tertiary French centers will participate in the present study. The overall inclusion study period will be 2 years, overall study duration will be 5 years. Patients greater than 35 years old, diagnosed with suspicious uterine tumor and needing surgical intervention will be included. Uterine tumors will be considered as suspicious in case of rapid tumor growth (≥30% of the maximum diameter in 1-year interval), symptomatic tumors in postmenopausal women, tumors characterized by certain suspicious ultrasound criteria history of treatment with tamoxifen and genetical predisposal to cancer syndromes. Included patients will undergo preoperatively a Vaginal Ultrasound-Guided Biopsy (VUGB). There will be two histopathological diagnoses for each patient, the first based on the biopsy specimen received preoperatively (Index test) and the second based on the surgical specimen of uterus resected 'en block'. These diagnoses will be compared in order to assess diagnostic performance of VUGB. Histological criteria used for both diagnoses will be that of Bell et al which were revised by OMS 2014 classification. Results: Our primary study hypothesis is that diagnostic performance of VUBG is capable to differentiate fibroma and sarcoma with a sensitivity greater than 90%. Considering as acceptable a sensitivity of 90% (H0) and excellent a sensitivity of 95% (H1), a sample size of 250 patients would be necessary to achieve 80% statistical power with a 5% type-1 statistical error. Taking into account a potential drop-out rate of 10%, there will needed 275 subjects to be included in our study. Primary study endpoint is sensitivity of VUGB anatomopathological diagnosis. Secondary endpoints include specificity, accuracy Youden's index, positive and negative predictive values. Conclusion: In case VUGB is demonstrated to be effective and safe to make the differential diagnosis, this should permit preoperatively the stratification of patients to either laparotomy for sarcomas or minimally invasive surgery for benign myomas. Therefore, both unnecessary laparotomies and cancer-spoilage by sarcoma morcellations could be avoided at the maximum degree. Disclosures: Authors have nothing to disclose